Democracy Education for Children using a Cartoon Video and Mock Voting - Jun Makita (International Journal of Asian Education, 2021)
In democracy education, determining how best to teach young children about democracy and how to measure the effectiveness of such learning is difficult, as "democracy" is a subjective and intangible concept. Given the challenge that this presents to educational planners, the author has created a cartoon video about democracy accompanied by an opportunity for children who watch the video to "mock vote." The author used the video in a series of elementary school visits to teach the children the meaning of democracy. The effects of the video learning were assessed by analyzing the children's questionnaire responses before and after the class using text data mining. It was found that the children were able to assimilate the contents of the video and the themes behind the story; that is, they understood the meaning of democracy and democratic elections.